2021
DOI: 10.3390/biology10090885
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Sugar Assimilation for Lipid Production in Aspergillus oryzae BCC7051 through Comparative Transcriptome Perspective

Abstract: Microbial lipid production with cost effectiveness is a prerequisite for the oleochemical sector. In this work, genome-wide transcriptional responses on the utilization of xylose and glucose in oleaginous Aspergillus oryzae were studied with relation to growth and lipid phenotypic traits. Comparative analysis of the active growth (t1) and lipid-accumulating (t2) stages showed that the C5 cultures efficiently consumed carbon sources for biomass and lipid production comparable to the C6 cultures. By pairwise com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
5
1
Order By: Relevance
“…41,42 On the other hand, A. oryzae biomass cultivated in PDB medium had 30.24% protein, 28.47% carbohydrate, and 25.12% lipid (Table 4). The value in A. oryzae biomassderived lipid content was lower than that stated by Kaur and Worgan but was higher than the one reported by Vorapreeda et al 43,44 With respect to the fatty acid composition, A. oryzae lipid had 25.79% PA, 11.18% stearic acid (C18:0, SA), 15.48% oleic acid (C18:1, OA), and 27.14% LA as the main fatty acids, as shown in Table 4. C16 and C18 fatty acids of A. oryzae lipid represented around 95%, manifesting that A. oryzae could synthesize valuable lipids with superior quality for biodiesel production.…”
Section: T H Icontrasting
confidence: 68%
See 1 more Smart Citation
“…41,42 On the other hand, A. oryzae biomass cultivated in PDB medium had 30.24% protein, 28.47% carbohydrate, and 25.12% lipid (Table 4). The value in A. oryzae biomassderived lipid content was lower than that stated by Kaur and Worgan but was higher than the one reported by Vorapreeda et al 43,44 With respect to the fatty acid composition, A. oryzae lipid had 25.79% PA, 11.18% stearic acid (C18:0, SA), 15.48% oleic acid (C18:1, OA), and 27.14% LA as the main fatty acids, as shown in Table 4. C16 and C18 fatty acids of A. oryzae lipid represented around 95%, manifesting that A. oryzae could synthesize valuable lipids with superior quality for biodiesel production.…”
Section: T H Icontrasting
confidence: 68%
“…The value in A. oryzae biomass-derived lipid content was lower than that stated by Kaur and Worgan but was higher than the one reported by Vorapreeda et al , With respect to the fatty acid composition, A. oryzae lipid had 25.79% PA, 11.18% stearic acid (C18:0, SA), 15.48% oleic acid (C18:1, OA), and 27.14% LA as the main fatty acids, as shown in Table .…”
Section: Resultsmentioning
confidence: 51%
“…Deoxyribose-phosphate aldolase was reduced in abundance by −2.3 fold and had a role in gluconeogenesis and the glyoxylate cycle [ 43 ]. Decreased abundance of methyltransferase LaeA-like putative protein −2.16 fold could explain the downregulation of proteins associated with specific secondary metabolites [ 44 ], including helvolic acid and fumagillin. Proteins associated with helvolic acid biosynthesis, including cytochrome P450 monooxygenase helB1 (−2.8 fold), short chain dehydrogenase helC (−3.8 fold), protostadienol synthase helA (−2.8 fold) and 3-ketosteroid 1-dehydrogenase helE (−2.4 fold) were decreased in abundance and the fumagillin associated protein polyketide transferase af380 (−3.8 fold) was also decreased in abundance [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glycerol had a positive impact on fumaric acid production, while xylose exhibited no significant effect. A comparative analysis of the active growth and lipid accumulation stages of A. oryzae BCC7051 also revealed that this strain exhibited greater efficiency in utilizing carbon sources to produce biomass and lipids in the C5 (xylose) medium compared to a C6 (glucose) medium [86]. Furthermore, when a mixture of glucose and xylose was used as the carbon source in the medium, an increased glucose ratio correspondingly increased the kojic acid yield from A. oryzae BCC7051.…”
Section: The Impact Of Carbon Sourcesmentioning
confidence: 92%